#TITLE_ALTERNATIVE# - Fithratur Rahman - Nim: 15112086, Fuad
RTK (Real-time Kinematic) is a real-time differential positioning system by using phase-range data. Performance of RTK GPS method relies on several defining factor, one of them is the length of baseline that lies between base and rover. As it increases, it is harder for ambiguity resolution, atmosperic bias, and orbita error to be estimated correctly. This research aims to determine the level of accuracy, precision, and reliability of RTK GPS method for short Ã‚Â– long baseline using mobile CORS. The measurement were done using NavCom RTK GPS receiver SF3040 type with the distance between base and rover is around 5 km to 83.5 km, 10 km with observed baseline length interval. The level of accuracy is obtained by comparing the RTK coordinates with reference coordinates. The result of this research shows that the level of horizontal accuracy for baseline length shortest to longest baseline is about 1 to 42 cm for horizontal accuracy and 10 to 45 cm for vertical accuracy. Low level of accuray that occurs on several baseline (such as 17.7 km and 36.34 km) mostly are caused by high amount of ionospheric bias and multipath. The level of reliability is obtained by comparing fixed solution amount with the total number of solutuion at given baseline. From 30 minutes observation time with 3 to 5 seconds of observation interval, the method reliability of producing fixed solution is 73.5% until 83.5 km baseline length.